The Therapeutic Potential of Mangosteen Pericarp as an Adjunctive Therapy for Bipolar Disorder and Schizophrenia - Ashton, Melanie M.; Dean, Olivia M.; Walker, Adam J.; Bortolasci, Chiara C.; Ng, Chee H.; Hopwood, Malcolm; Harvey, Brian H.; Möller, Marisa; McGrath, John J.; Marx, Wolfgang; Turner, Alyna; Dodd, Seetal; et al. (Frontiers in Psychiatry, 2019)
There is great need for new treatments for serious mental illnesses such as bipolar disorder and schizophrenia. This review proposes that Garcinia mangostana Linn. (mangosteen) pericarp is a possible agent for therapeutic use for these disorders. Research to date demonstrates neurobiological properties of the mangosteen pericarp that are well aligned with the current understanding of the pathophysiology of bipolar disorder and schizophrenia. Mangosteen pericarp has demonstrated antioxidant, putative neuroprotective, anti-inflammatory and putative mitochondrial enhancing properties, with animal studies demonstrating favorable pharmacotherapeutic benefits with respect to bipolar disorder and schizophrenia. This review summarizes evidence of its properties and supports the case for future studies to assess the utility of mangosteen pericarp as an adjunctive treatment option for bipolar disorder and schizophrenia.